Time in the theory of the psychic as a process S. L. Rubinstein - Polikarpov, Vladimir A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The theory of the psychic as a process is considered. Rubinstein, as a methodological basis of modern psychology, its development by the Russian psychologist A. V. Brushlinsky. The specificity of the theory, defined by the central category «process» and a unique solution to the problem of determinism, is singled out. An original approach to solving the problem of the nature of time is proposed. The visible image of time is in the dynamics of interaction of the process and its result. All the newly emerging determinants that influence the process, making it irreversible, unpredictable, unidirectional, is time acting as a general principle of self-determination of all world processes. Reduction of time to the fundamental mechanisms of causality, to the mechanisms of interaction between the process and the results generated by it, often translating it into another quality, we get a dynamic, relational concept of time.